ANALISIS IKLAN MEDIA DIGITAL DAN KUALITAS INFORMASI TERHADAP KEPUTUSAN PEMBELIAN PADA SITUS E-COMMERCE BLIBLI - Suali, Suali (JURSIMA, 2022)
The purpose of this study is to determine whether digital media advertising and information quality have an influence on purchasing decisions. This study uses primary data to prove the hypothesis, data collection through questionnaires. The population in this study is the people of Batam City with a sample of 100 respondents. Data analysis methods used in this study include quantitative analysis, descriptive statistical tests, data quality tests, classical assumption tests, influence tests, and hypothesis tests processed using SPSS 27.0 software. Partially, the results of this study indicate that information quality has a positive and significant influence on purchasing decisions, while digital media advertising does not have a significant influence on purchasing decisions. Simultaneously, the results of the study indicate that the variables of digital media advertising and information quality have a positive and significant influence on purchasing decisions.